NFT for healthcare game clinical trials - Zhang, Zili (Nanyang Technological University, 2023)
The rise of healthcare games has presented promising avenues for enhancing patient engagement, treatment adherence, and health outcomes. However, the prolonged FDA clinical trials process poses significant impediments, curtailing the agile development and iterative improvement of these games. Traditional methods, characterized by extensive timelines and rigid protocols, are proving incompatible with the dynamic and rapidly evolving nature of game development. This paper delves into an explorative study on harnessing blockchain and Web3 technology as a solution to these challenges.